Age-related differences in patterns of criminal activity among a large sample of polydrug injectors in Australia - Horyniak, D.; Dietze, P.; Degenhardt, L.; Agius, P.; Higgs, Peter; Bruno, R.; Alati, R.; Burns, L. (Informa Healthcare, 2014)
Background: The relationship between age and criminal activity among drug-using populations is poorly understood. Methods: Data from 10 years of repeat cross-sectional surveys of sentinel samples of regular people who inject drugs (PWID) across Australia (n=5844) were used to explore the relationship between age and past-month drug dealing, property crime and violent crime, and past-year arrest. Descriptive statistics were used to explore the prevalence and frequency of each outcome. The relationship between age and each outcome was measured using multivariable Poisson regression with robust error variance. Results: After adjusting for confounding factors, each 5-year increase in age was associated with significant reductions in drug dealing (adjusted incidence rate ratio [AIRR]: 0.90, 95% confidence interval [CI]: 0.87–0.94), property crime (AIRR: 0.85, 95% CI: 0.82–0.89) and violent crime (AIRR: 0.77, 95% CI: 0.70–0.85). Older participants were also significantly less likely to report being arrested in the past 12 months (AIRR: 0.91, 95% CI: 0.88–0.93). Conclusions: Younger PWID are more heavily involved in criminal activity compared with their older counterparts. This study highlights the need for early intervention programmes to prevent offending behaviour becoming entrenched, as well as continued efforts to redirect young PWID away from the criminal justice system and into treatment and education programmes.